Alloying modification method of platinum catalyst and application of alloying modification method

The Pt-Fe-NPC catalyst prepared by the alloying modification method solves the problems of high usage, high cost and poor stability of existing fuel cell catalysts, achieves high activity, low cost and long-term stable operation effects, and shows excellent performance in zinc-air batteries.

CN119786630AActive Publication Date: 2025-04-08CHONGQING UNIV OF ARTS & SCI

Patent Information

Application Number
CN202510096584.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-08
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Existing fuel cell catalysts have problems such as high usage of precious metals, high cost, poor stability, and reduced stability and activity of non-precious metal catalysts in high temperature or high humidity environments, which limits their application in high power, large-scale, long-term and stable operating environments.

Method used

After uniformly mixing the platinum carbon catalyst with the phytic acid solution and lyophilized, it undergoes pyrolysis and sulfuric acid treatment, and then uniformly mixing with ferrous sulfate and 1,10-phenanthroline, and undergoes secondary pyrolysis and sulfuric acid treatment, a Pt-Fe-NPC catalyst is prepared to form a three-dimensional porous structure and a ferroplatin alloy, thereby improving the activity and stability of the catalyst.

Benefits of technology

It effectively improves the activity and stability of the catalyst, reduces the use of precious metal platinum, reduces the manufacturing cost, and shows high energy density and long-term constant current density discharge capabilities in zinc-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786630A_ABST
    Figure CN119786630A_ABST
Patent Text Reader

Abstract

The invention provides an alloying modification method of a platinum catalyst, and relates to the field of electrochemical catalysis, and the alloying modification method specifically comprises the following steps: uniformly mixing a 5% platinum-carbon catalyst and a phytic acid solution, carrying out freeze-drying treatment, carrying out primary pyrolysis, sulfuric acid treatment, ultrapure water cleaning and suction filtration, and drying to obtain powder, adding ferrous sulfate and 1, 10-phenanthroline, and uniformly stirring to obtain the platinum-carbon alloy. And carrying out secondary pyrolysis, sulfuric acid treatment, ultrapure water cleaning, suction filtration and drying to obtain the alloying modified carbon-based catalyst. According to the method, the metal platinum and the transition metal are alloyed, so that the activity and the stability of the catalyst are effectively improved, the usage amount of the noble metal platinum is reduced, and the manufacturing cost of the catalyst is effectively reduced; the alloying modified carbon-based catalyst obtained by the method can be used for preparing primary zinc-air batteries, rechargeable zinc-air batteries and other batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical catalysis, and in particular to an alloying modification method of a platinum catalyst and application thereof. Background Art

[0002] Hydrogen fuel cells have become one of the key focuses in the field of energy conversion due to their high energy density, environmental friendliness and abundant raw material resources. The performance of hydrogen fuel cells mainly depends on the air electrode, which undergoes a slow oxygen reduction reaction (ORR) during the discharge process, consuming electrons from the fuel, thereby directly converting chemical energy into electrical energy. Therefore, some cars have been equipped with fuel cells as a power source and have been mass-produced. In the existing technology, there are many types of fuel cell cathode catalysts, and high catalytic activity, high stability and low cost have become the main directions for synthesizing catalysts. In current research, fuel cell catalysts are mainly divided into two categories: one is precious metal catalyst materials, including Pt, Pd, Au, etc.; the other is non-precious metal catalysts, including transition metals and heteroatom-doped carbon materials. The use of precious metals as catalysts can significantly improve the electrocatalytic performance of ORR, but precious metals are not only expensive, but also have disadvantages such as poor resistance to toxicity and poor stability, which seriously limit the large-scale application of precious metal-based catalysts in the field of fuel cells; the use of non-precious metals as catalysts, although it can effectively reduce the cost of catalysts, has low catalytic activity and poor stability (for example, Fe-NC catalysts may experience deactivation of Fe active sites, corrosion of C, and collapse of the catalyst three-phase interface during operation in hydrogen fuel cells), difficulty in mass production, and high requirements for the working environment (for example, in high temperature or high humidity environments, the stability and activity of some non-precious metal catalysts may decrease significantly). These problems make it impossible to use non-precious metals in high-power, large-scale, long-term stable operation environments, which seriously restricts the application of non-precious metal catalysts in fuel cells. Summary of the invention

[0003] In view of the problems existing in the above prior art, the object of the present invention is to provide a method for alloying and modifying a platinum catalyst, which not only effectively improves the activity and stability of the catalyst by alloying metallic platinum with a transition metal, but also reduces the usage of precious metal platinum and effectively reduces the manufacturing cost of the catalyst.

[0004] Another object of the present invention is to provide applications of the above-mentioned platinum catalyst after alloying and modification.

[0005] The purpose of the present invention is achieved through the following technical solutions: A method for alloying and modifying a platinum catalyst, comprising: Step S1, uniformly mixing and stirring a 5% platinum-carbon catalyst, a phytic acid solution and deionized water, and then freeze-drying the mixed solution; Step S2, pyrolyzing the freeze-dried powder in step S1, treating the product after the pyrolysis with sulfuric acid, then washing with ultrapure water, filtering, and drying; Step S3, uniformly mixing the powder dried in step S2 with ferrous sulfate and 1,10-phenanthroline, and then performing secondary pyrolysis; Step S4, treating the product of the secondary pyrolysis in step S3 with sulfuric acid, then washing with ultrapure water, filtering, and drying to obtain an alloyed modified carbon-based catalyst (ie, Pt-Fe-NPC catalyst).

[0006] Based on further optimization of the above scheme, the phytic acid solution in step S1 is a phytic acid solution with a mass concentration of 70%; the mass volume ratio of 5% platinum carbon catalyst, phytic acid solution and deionized water is: 0.1-0.3 g: 0.5-1.5 mL: 8-12 mL.

[0007] Based on further optimization of the above scheme, the stirring time of the 5% platinum-carbon catalyst and the phytic acid solution in step S1 is 12 to 24 hours.

[0008] Based on further optimization of the above scheme, the freeze-drying step in step S1 is specifically as follows: pre-freeze the mixed solution at a temperature of -15°C to -10°C for 2 hours, and then put it into a vacuum freeze dryer at a temperature of -55°C to -45°C for freeze-drying for 12 hours.

[0009] Based on further optimization of the above scheme, the specific steps of the primary pyrolysis in step S2 are: heating to 800-1000° C. at a rate of 3-5° C. / min, and then keeping the temperature for 1-2 hours to complete the primary pyrolysis.

[0010] Based on further optimization of the above scheme, the mass ratio of the dried powder, ferrous sulfate, and 1,10-phenanthroline in step S3 is 30-50 mg: 0.012-0.014 mg: 0.026-0.028 mg.

[0011] Based on further optimization of the above scheme, the specific steps of the secondary pyrolysis in step S3 are: heating to 800-1000° C. at a rate of 3.5-4.5° C. / min, and then keeping the temperature for 1-2 hours to complete the secondary pyrolysis.

[0012] Based on further optimization of the above scheme, the sulfuric acid treatment in step S2 and step S4 is specifically as follows: placing the pyrolysis product into a 0.5-2 mol / L sulfuric acid solution and stirring at a temperature of 60-80° C. for 10-12 hours.

[0013] Based on further optimization of the above scheme, the drying step in step S2 and step S4 is specifically as follows: placing the sample obtained after filtration into a forced air drying oven at 55°C to 65°C and drying for 6 hours.

[0014] Based on the above preparation method, the present invention also provides an application of an alloyed modified platinum catalyst, specifically an application of a Pt-Fe-NPC catalyst in a zinc-air battery. The Pt-Fe-NPC catalyst can be used in the preparation process of a primary zinc-air battery or a rechargeable zinc-air battery.

[0015] The following are the technical effects of the present invention: The present invention uniformly mixes 5% of the platinum-carbon catalyst with a phytic acid solution, freeze-dries the mixture, and then performs a pyrolysis, and then performs a secondary pyrolysis after uniformly mixing ferrous sulfate and 1,10-phenanthroline. This not only effectively improves the morphological characteristics of the platinum-carbon catalyst and forms a precursor with a three-dimensional porous structure (i.e., a hierarchical pore structure in which micropores and mesoporous structures are uniformly distributed on the surface of the carbon material), but also facilitates the adsorption of Fe ions by the carbon matrix material and facilitates the transportation and transfer of reactants and products. It also effectively ensures the uniform distribution of active sites, avoids the agglomeration of active sites during the pyrolysis process, and avoids the problems of site deactivation, poor stability, poor ORR activity, etc. caused by uneven active sites. In addition, it also promotes the full combination of Fe ions and Pt atoms to form an iron-platinum alloy, thereby using the iron-platinum alloy as an anchor point to anchor platinum nanoparticles, avoiding their dissolution and migration during the ORR reaction, effectively ensuring the stability of the catalyst, and improving the catalytic activity of the catalyst and the corresponding battery performance.

[0016] The carbon-based catalyst prepared by alloying modification has a specific surface area of ​​up to 1139.2 m² / g or more and exhibits excellent ORR activity: E 1 / 2 =0.851V vs.RHE; the catalyst was used as a positive electrode oxygen reduction catalyst to assemble a primary zinc-air battery, which has a high energy density of not less than 926Wh / kg-1 Zn. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of the alloyed modified catalyst prepared in Example 2 of the present invention.

[0018] Figure 2 This is a TEM image of the alloyed modified catalyst prepared in Example 2 of the present invention.

[0019] Figure 3 This is the HR-TEM image of the alloyed modified catalyst prepared in Example 2 of the present invention.

[0020] Figure 4This is the XRD diagram of the alloyed modified catalyst prepared in Example 2 of the present invention.

[0021] Figure 5 This is the XPS graph of the alloyed modified catalyst prepared in Example 2 of the present invention.

[0022] Figure 6 is the N of the alloyed modified catalyst prepared in Example 2 of the present invention 2 Adsorption-desorption isotherm diagram (inset shows pore distribution).

[0023] Figure 7 This is a comparison chart of the oxygen reduction LSV of the alloyed modified catalyst prepared in Example 2 of the present invention and the Pt / C catalyst.

[0024] Figure 8 This is a comparison chart of the energy density of a primary zinc-air battery assembled with the alloyed modified catalyst prepared in Example 2 of the present invention and the Pt / C catalyst.

[0025] Fig. 9 This is a long-term constant current density discharge diagram of a primary zinc-air battery assembled with the alloyed modified catalyst prepared in Example 2 of the present invention.

[0026] Fig.10 This is a comparison chart of the charge / discharge cycle test of a rechargeable zinc-air battery assembled with the alloyed modified catalyst prepared in Example 2 of the present invention and the Pt / C catalyst. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0028] Embodiment 1: A platinum catalyst alloying modification method comprising: Step S1, uniformly mix 5% platinum-carbon catalyst (Shanghai Aladdin Biochemical Technology Co., Ltd., commercially available product), 70% phytic acid solution (Shanghai McLean Biochemical Technology Co., Ltd., commercially available product) and deionized water, and stir for 12 hours, wherein the amount of platinum-carbon catalyst is 0.15 g, the amount of phytic acid solution is 0.5 mL, and the amount of deionized water is 8 mL; then freeze-dry the mixed solution, and the freeze-drying step is specifically as follows: pre-freeze the mixed solution at a temperature of -10°C for 2 hours, and then put it into a vacuum freeze dryer at a temperature of -45°C and freeze-dry for 12 hours.

[0029] Step S2, subjecting the freeze-dried powder in step S1 to a pyrolysis step, specifically: heating to 800°C at a rate of 3°C / min, and then keeping the temperature for 2h to complete the pyrolysis step; The product after the primary pyrolysis is treated with sulfuric acid, specifically: the product after the primary pyrolysis is placed in a 0.5 mol / L sulfuric acid solution and stirred at 60°C for 12 hours; The sample was then washed with ultrapure water and filtered, and then dried. The drying step was as follows: the sample obtained after filtration was placed in a 55°C forced air drying oven and dried for 6 hours.

[0030] Step S3, uniformly mixing the dried powder in step S2 with ferrous sulfate (AR, a commercial product of Shanghai Aladdin Biochemical Technology Co., Ltd.) and 1,10-phenanthroline (99%, a commercial product of Shanghai Titan Technology Co., Ltd.), wherein the mass ratio of the dried powder, ferrous sulfate and 1,10-phenanthroline is 30 mg: 0.012 mg: 0.026 mg; and then performing secondary pyrolysis, specifically: heating to 800° C. at a rate of 3.5° C. / min, and then keeping warm for 2 hours to complete the secondary pyrolysis.

[0031] Step S4, subjecting the product of the secondary pyrolysis in step S3 to sulfuric acid treatment, specifically: placing the pyrolysis product in a 0.5 mol / L sulfuric acid solution and stirring at 60° C. for 12 h; Then, the sample was washed with ultrapure water and filtered, and then dried. The specific drying step was as follows: the sample obtained after filtration was placed in a 55°C forced air drying oven and dried for 6 hours to obtain an alloyed modified carbon-based catalyst (i.e., Pt-Fe-NPC catalyst).

[0032] The specific surface area of ​​the carbon-based catalyst obtained by alloying in this embodiment is: 1227.8m² / g, and the ORR activity is: E 1 / 2 =0.834V vs.RHE.

[0033] Embodiment 2: A method for alloying and modifying a platinum catalyst, comprising: Step S1, uniformly mix 5% platinum-carbon catalyst (Shanghai Aladdin Biochemical Technology Co., Ltd., commercially available product), 70% phytic acid solution (Shanghai McLean Biochemical Technology Co., Ltd., commercially available product) and deionized water, and stir for 18 hours, wherein the amount of platinum-carbon catalyst is 0.2 g, the amount of phytic acid solution is 1 mL, and the amount of deionized water is 10 mL; then freeze-dry the mixed solution, and the freeze-drying step is specifically as follows: pre-freeze the mixed solution at a temperature of -12°C for 2 hours, and then put it into a vacuum freeze dryer at a temperature of -50°C and freeze-dry for 12 hours.

[0034] Step S2, subjecting the freeze-dried powder in step S1 to a pyrolysis step, specifically: heating to 900° C. at a rate of 4° C. / min, and then keeping the temperature for 1.5 h to complete the pyrolysis step; The product after the primary pyrolysis is treated with sulfuric acid, specifically: the product after the primary pyrolysis is placed in a 1 mol / L sulfuric acid solution and stirred at 70°C for 11 hours; The sample was then washed and filtered with ultrapure water and then dried. The drying step was as follows: the sample obtained after filtration was placed in a 60°C forced air drying oven and dried for 6 hours.

[0035] Step S3, uniformly mixing the dried powder in step S2 with ferrous sulfate (AR, a commercial product of Shanghai Aladdin Biochemical Technology Co., Ltd.) and 1,10-phenanthroline (99%, a commercial product of Shanghai Titan Technology Co., Ltd.), wherein the mass ratio of the dried powder, ferrous sulfate and 1,10-phenanthroline is 40 mg: 0.013 mg: 0.027 mg; and then performing secondary pyrolysis, specifically: heating to 900° C. at a rate of 4° C. / min, and then keeping warm for 1.5 h to complete the secondary pyrolysis.

[0036] Step S4, subjecting the product of the secondary pyrolysis in step S3 to sulfuric acid treatment, specifically: placing the pyrolysis product in a 1 mol / L sulfuric acid solution and stirring at 70° C. for 11 h; Then, the sample was washed with ultrapure water and filtered, and then dried. The drying step was as follows: the sample obtained after filtration was placed in a 60°C forced air drying oven and dried for 6 hours to obtain an alloyed modified carbon-based catalyst (ie, Pt-Fe-NPC catalyst).

[0037] The specific surface area of ​​the carbon-based catalyst obtained by alloying in this embodiment is: 1139.2m² / g, and the ORR activity is: E 1 / 2 =0.851V vs.RHE.

[0038] The carbon-based catalyst obtained by alloying modification in the embodiment was analyzed. Figure 1 The SEM image shows that the catalyst has a three-dimensional morphology with a rich porous structure, and it can also be seen that part of the iron-platinum alloy is distributed on the catalyst surface. Figure 2 The TEM image shows that the catalyst forms a three-dimensional porous structure and contains a large amount of relatively dispersed iron-platinum alloy. Figure 3 The high-resolution transmission electron microscopy (HR-TEM) image shows irregular lattice fringes, indicating that the carbon matrix has an amorphous nature, and the selected area electron diffraction pattern in the inset also proves the presence of iron-platinum alloy in the entire carbon matrix. Figure 4 The X-ray diffraction pattern of further proves the existence of iron-platinum alloy. Figure 5The X-ray photoelectron spectroscopy test graph clearly shows that the content of M-Nx active sites in the catalyst is as high as 29.2%, proving the existence of high-content active sites, which effectively improves the catalytic activity of the catalyst. Figure 6 It can be seen that the catalyst exhibits a typical type IV nitrogen adsorption-desorption isotherm, and the pore size distribution shows that the catalyst has a multi-level pore structure and its specific surface area is as high as 1139.2m 2 / g, which is beneficial to expose more active sites and accelerate electron transfer and mass transfer rate. Figure 7 The LSV curves show the excellent electrochemical performance of the catalyst. It is obvious that the catalyst (E 1 / 2 = 0.856 V vs. RHE, J L = 5.86 mA cm -2 ) and 20% Pt / C (E 1 / 2 = 0.8561V vs. RHE, J L = 5.3 mA cm -2 ) has a comparable ORR activity, and the Pt content in the catalyst obtained by the alloying modification method in this embodiment is less, not higher than 5%, and the cost is lower.

[0039] Embodiment 3: A platinum catalyst alloying modification method comprising: Step S1, uniformly mix 5% platinum-carbon catalyst (Shanghai Aladdin Biochemical Technology Co., Ltd., commercially available product), 70% phytic acid solution (Shanghai McLean Biochemical Technology Co., Ltd., commercially available product) and deionized water, and stir for 24 hours, wherein the amount of platinum-carbon catalyst is 0.3 g, the amount of phytic acid solution is 1.5 mL, and the amount of deionized water is 12 mL; then freeze-dry the mixed solution, and the freeze-drying step is specifically as follows: pre-freeze the mixed solution at a temperature of -15°C for 2 hours, and then put it into a vacuum freeze dryer at a temperature of -55°C and freeze-dry for 12 hours.

[0040] Step S2, subjecting the freeze-dried powder in step S1 to a pyrolysis step, specifically: heating to 1000° C. at a rate of 5° C. / min, and then keeping the temperature for 1 hour to complete the pyrolysis step; The product after the primary pyrolysis is treated with sulfuric acid, specifically: the product after the primary pyrolysis is placed in a 2 mol / L sulfuric acid solution and stirred at 80°C for 10 hours; The sample was then washed and filtered with ultrapure water and then dried. The drying step was as follows: the sample obtained after filtration was placed in a 65°C forced air drying oven and dried for 6 hours.

[0041] Step S3, uniformly mixing the dried powder in step S2 with ferrous sulfate (AR, a commercial product of Shanghai Aladdin Biochemical Technology Co., Ltd.) and 1,10-phenanthroline (99%, a commercial product of Shanghai Titan Technology Co., Ltd.), wherein the mass ratio of the dried powder, ferrous sulfate and 1,10-phenanthroline is 50 mg: 0.014 mg: 0.028 mg; and then performing secondary pyrolysis, specifically: heating to 1000° C. at a rate of 4.5° C. / min, and then keeping warm for 1 hour to complete the secondary pyrolysis.

[0042] Step S4, subjecting the product of the secondary pyrolysis in step S3 to sulfuric acid treatment, specifically: placing the pyrolysis product in a 2 mol / L sulfuric acid solution and stirring at 80° C. for 10 h; Then, the sample was washed with ultrapure water and filtered, and then dried. The drying step was as follows: the sample obtained after filtration was placed in a 65°C forced air drying oven and dried for 6 hours to obtain an alloyed modified carbon-based catalyst (ie, Pt-Fe-NPC catalyst).

[0043] The specific surface area of ​​the carbon-based catalyst obtained by alloying in this embodiment is: 1349.2m² / g, and the ORR activity is: E 1 / 2 =0.842V vs.RHE.

[0044] Comparative Example 1: A method for preparing a carbon-based catalyst comprises: Step S1, 5% platinum-carbon catalyst (Shanghai Aladdin Biochemical Technology Co., Ltd., commercially available product), etchant (using existing conventional etchant, including but not limited to zinc chloride solution, ammonium chloride solution, sodium bicarbonate solution, ammonium bicarbonate solution) and deionized water are uniformly mixed and stirred for 18 hours, wherein the amount of platinum-carbon catalyst is 0.2 g, and the amount of etchant is an etchant of the same mass as phytic acid in Example 2 dissolved in 10 mL of deionized water; then the mixed solution is freeze-dried, and the freeze-drying step is specifically as follows: the mixed solution is pre-frozen at a temperature of -12°C for 2 hours, and then placed in a vacuum freeze dryer at a temperature of -50°C and freeze-dried for 12 hours.

[0045] Step S2 is consistent with step S2 in embodiment 2; Step S3 is consistent with step S3 in embodiment 2; Step S4 is consistent with step S4 in embodiment 2.

[0046] In this comparative example (using zinc chloride solution, ammonium chloride solution, sodium bicarbonate solution, and ammonium bicarbonate solution as etchants, respectively), the specific surface areas of the carbon-based catalysts prepared are 462.5 m² / g, 628.3 m² / g, 366.8 m² / g, and 481.7 m² / g, respectively, and the ORR activities are: E1 / 2 =0.75V vs.RHE, E 1 / 2 =0.77V vs.RHE, E 1 / 2 =0.81V vs.RHE, E 1 / 2 =0.79V vs.RHE, and the active site contents are 15.7%, 17.2%, 11.9%, and 19.4%, respectively.

[0047] Comparative Example 2: A method for preparing a carbon-based catalyst comprises: Step S1, 5% platinum carbon catalyst (Shanghai Aladdin Biochemical Technology Co., Ltd., commercially available product), 70% mass concentration of phytic acid solution (Shanghai McLean Biochemical Technology Co., Ltd., commercially available product) and deionized water are uniformly mixed and stirred for 18 hours, wherein the amount of platinum carbon catalyst is 0.2g, the amount of phytic acid solution is 1mL, and the amount of deionized water is 10mL; then the mixed solution is dried, and the drying is carried out by conventional drying (i.e., placed in a 60°C forced air drying oven for drying until powder is obtained).

[0048] Step S2 is consistent with step S2 in embodiment 2; Step S3 is consistent with step S3 in embodiment 2; Step S4 is consistent with step S4 in embodiment 2.

[0049] The specific surface area of ​​the carbon-based catalyst prepared in this comparative example is: 990.6m² / g, and the ORR activity is: E 1 / 2 =0.83V vs.RHE, active site content: 23.2%.

[0050] Comparative Example 3: A method for preparing a carbon-based catalyst comprises: Step S1 is consistent with step S1 in embodiment 2; Step S2, uniformly mixing the freeze-dried powder in step S1 with ferrous sulfate (Shanghai Aladdin Biochemical Technology Co., Ltd. AR, commercially available product) and 1,10-phenanthroline (Shanghai Titan Technology Co., Ltd. 99%, commercially available product), wherein the mass ratio of the freeze-dried powder, ferrous sulfate, and 1,10-phenanthroline is 40 mg: 0.013 mg: 0.027 mg; and then performing pyrolysis, specifically: heating to 900° C. at a rate of 4° C. / min, and then keeping warm for 1.5 hours to complete the pyrolysis.

[0051] Step S3 is consistent with step S4 in embodiment 2. The specific surface area of ​​the carbon-based catalyst prepared in this comparative example is: 1036.7m² / g, and the ORR activity is: E 1 / 2=0.79V vs.RHE, and the active site content is 14.6%.

[0052] Embodiment 4: An application of a platinum catalyst alloying modification method, specifically an application in the preparation of a primary zinc-air battery, comprising: Weigh 2 mg of the carbon-based catalyst prepared by the alloying modification method in Example 2 and evenly disperse it in a mixed solution consisting of 195 μL of ethanol and 5 μL of naphthol; then evenly apply the mixed solution on a 4 cm 2 A carbon cloth was used as the positive electrode oxygen reduction catalyst, a zinc sheet with a thickness of 0.2 mm was selected as the negative electrode, and a 6 mol / L KOH solution was used as the electrolyte to assemble a primary zinc-air battery.

[0053] Control group: A Pt / C catalyst with a platinum content of 20% (i.e., an existing commercially available Pt / C catalyst) was used to replace the carbon-based catalyst prepared by the alloying modification method in Example 2, and a primary zinc-air battery was assembled and prepared using the same method as above.

[0054] Figure 8 This is a comparison chart of the energy density of a primary zinc-air battery assembled with a carbon-based catalyst prepared by the alloying modification method in Example 2 and a Pt / C catalyst with a platinum content of 20%; Figure 8 It can be clearly seen that at a fixed current density of 50dmA / cm 2 When discharged at low temperatures, the primary zinc-air battery assembled by iron-platinum alloy doped with carbon-based catalyst has a high energy density of 926 Wh / kg-1 Zn, which is far higher than the energy density of the primary zinc-air battery assembled by Pt / C with a platinum content of 20%, that is, 770 Wh / kg-1Zn.

[0055] Fig. 9 The primary zinc-air battery prepared in this example is subjected to a fixed current density of 50 mA / cm 2 It can be clearly seen from the long-term constant current density discharge diagram under the condition of about 140h of constant current density discharge that the discharge voltage of a primary zinc-air battery assembled with the carbon-based catalyst prepared by the alloying modification method of the present invention only shows a decrease of 44 mV.

[0056] Embodiment 5: An application of a platinum catalyst alloying modification method, specifically an application in the preparation of a rechargeable and dischargeable zinc-air battery, comprising: Weigh 2 mg of the carbon-based catalyst prepared by the alloying modification method in Example 2 and 2 mg of RuO 2 , let them disperse evenly in a mixed solution consisting of 390μL of ethanol and 10μL of naphthol; then apply the mixed solution evenly on a 4cm2 The carbon cloth was used as the positive electrode oxygen reduction catalyst, and a zinc sheet with a thickness of 0.2 mm was selected as the negative electrode. KOH and Zn(Ac) 2 The mixed solution is used as the electrolyte to assemble a rechargeable zinc-air battery; wherein the concentration of KOH is 6 mol / L, Zn(Ac) 2 The concentration is 0.2 mol / L.

[0057] Control group: A Pt / C catalyst with a platinum content of 20% (i.e., an existing commercially available Pt / C catalyst) was used instead of the carbon-based catalyst prepared by the alloying modification method in Example 2, and a rechargeable zinc-air battery was assembled and prepared using the same method as above.

[0058] like Fig.10 As shown in the figure, the carbon-based catalyst and RuO prepared by the alloying modification method in this embodiment 2 During the charge and discharge process of more than 100 h, the discharge voltage of the assembled rechargeable zinc-air battery remained at 1.1926 V, the charge voltage remained at 1.9786 V, and the charge and discharge voltage difference was 78 mV; while the rechargeable zinc-air battery assembled with 20% Pt / C catalyst and RuO2 had a larger charge and discharge voltage difference of 90 mV, indicating that the carbon-based catalyst prepared by the alloying modification method has better long-term cycle stability when used in rechargeable zinc-air batteries.

Claims

1. A method for alloying and modifying a platinum catalyst, characterized in that: include: Step S1, uniformly mixing and stirring a 5% platinum-carbon catalyst, a phytic acid solution and deionized water, and then freeze-drying the mixed solution; Step S2, pyrolyzing the freeze-dried powder in step S1, treating the product after the pyrolysis with sulfuric acid, then washing with ultrapure water, filtering, and drying; Step S3, uniformly mixing the powder dried in step S2 with ferrous sulfate and 1,10-phenanthroline, and then performing secondary pyrolysis; Step S4, treating the product of the secondary pyrolysis in step S3 with sulfuric acid, then washing with ultrapure water, filtering, and drying to obtain an alloyed modified carbon-based catalyst.

2. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The phytic acid solution in step S1 is a phytic acid solution with a mass concentration of 70%; the mass volume ratio of 5% platinum-carbon catalyst, phytic acid solution and deionized water is: 0.1-0.3 g: 0.5-1.5 mL: 8 mL-12 mL.

3. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The stirring time of the 5% platinum-carbon catalyst and the phytic acid solution in step S1 is 12 to 24 hours.

4. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The specific steps of the primary pyrolysis in step S2 are: heating to 800-1000° C. at a rate of 3-5° C. / min, and then keeping the temperature for 1-2 hours to complete the primary pyrolysis.

5. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The mass ratio of the dried powder, ferrous sulfate and 1,10-phenanthroline in step S3 is 30-50 mg: 0.012-0.014 mg: 0.026~0.028mg.

6. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The specific steps of the secondary pyrolysis in step S3 are: heating to 800-1000° C. at a rate of 3.5-4.5° C. / min, and then keeping the temperature for 1-2 hours to complete the secondary pyrolysis.

7. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The sulfuric acid treatment in step S2 and step S4 is specifically as follows: placing the pyrolysis product into a 0.5-2 mol / L sulfuric acid solution and stirring at a temperature of 60-80° C. for 10-12 hours.

8. The alloying modification method of a platinum catalyst according to claim 1, characterized in that: The drying step in step S2 and step S4 is specifically as follows: placing the sample obtained after filtration in a forced air drying oven at 55° C. to 65° C. and drying for 6 hours.

Citation Information

Patent Citations

  • Preparation method of platinum-based alloy electrocatalyst and application

    CN108075140A

  • Bi-metal-based Fe-Co-N-S co-doped carbon catalyst, and preparation method and application therefor

    CN110444772A

  • Method for preparing carbon carrier loaded platinum-based nanoparticle catalyst under assistance of functional small molecules

    CN114904516A

  • Heterogeneous hydrogen catalyst reactor

    JP2012505810A

  • Catalyst for rechargeable energy storage devices and method for making the same

    US20220037675A1

Cited By

  • Hydrogen fuel cell catalyst, preparation method and application thereof

    CN121260823A

  • Preparation method of high-loading Pt-Co alloy catalyst

    CN121355277A